2002
DOI: 10.1111/1467-8624.00439
|View full text |Cite
|
Sign up to set email alerts
|

A Microgenetic/Cross‐Sectional Study of Matrix Completion: Comparing Short‐Term and Long‐Term Change

Abstract: A design that included both microgenetic and cross-sectional components was used to examine 135 Slovenian children's acquisition of matrix completion proficiency and compare microgenetic and age-related changes on the task. The microgenetic analyses indicated that children's errors became increasingly variable shortly before they discovered the correct strategy, that the correct strategy became dominant quite quickly following its initial use, that improvements in matrix completion performance generalized to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
174
5
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(198 citation statements)
references
References 50 publications
13
174
5
6
Order By: Relevance
“…These findings correspond with earlier literature reports (e.g., Resing & Elliott, 2011;Resing et al, 2015;Siegler & Svetina, 2002). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings correspond with earlier literature reports (e.g., Resing & Elliott, 2011;Resing et al, 2015;Siegler & Svetina, 2002). …”
Section: Discussionsupporting
confidence: 93%
“…Tzuriel & George, 2009). Another suggestion for future research, supported by the observed differential patterns of progression in performance and strategy quality, is that children in this young age group might require a more tailored form of scaffolded instruction and feedback (Davidson & Sternberg, 1984;Siegler & Svetina, 2002), operating within their zone of proximal development (Alibali & Goldin-Meadow, 1993;Granott, 2002;Wood, Bruner, & Ross, 1976). The transfer tasks should have this open character with "endless" possibilities, giving children a chance to spontaneously create analogies at their level of performance/thinking, which could subsequently be evaluated on the basis of their complexity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La variabilidad ha jugado un papel que ha oscilado entre la incomodidad y la promesa de ser la clave para entender el desarrollo (Miller, 2002;Puche-Navarro, 2003, 2008Siegler, 1995Siegler, , 2002aSiegler & Svetina, 2002van Dijk & van Geert, 2007;Yan & Fischer, 2002). La relación entre la variabilidad y procesos construcción del conocimiento, se consolida "como distintos itinerarios para acceder al conocimiento" (Rose & Fischer, 2009, p. 400).…”
Section: El Problema De La Variabilidadunclassified